Pengaruh Financial Distress Terhadap Penerimaan Opini Audit Going Concern Dengan Good Corporate Governance Sebagai Variabel Moderasi Studi Pada Sektor Energi Tahun 2014 – 2020 - Ismuninggar Suci; Imang Dapit Pamungkas (Jurnal Riset Ekonomi dan Bisnis, 2022)
This study examines the impact of financial distress on the going concern audit opinion and the moderator variables of good corporate governance. The purpose of the study shows that the influence of financial difficulties on audit opinions going concern and GCG can moderate the relation of financial difficulties in the audit opinion going concern. The object of energy sector research in 2014 - 2020 with a sample count of 273 purposive samplings. The quantitative method with analysis test tool using WarpPLS 7.0. The results of the analysis of data obtained in this study, namely financial distress have a negative effect on audit opinion going concern, and the proportion of independent board of commissioners and managerial ownership is unable to moderate financial distress on the receipt of audit opinion going concern. However, audit committees and institutional holdings are able to weaken the relationship of financial distress to audit opinion going concern.Studi ini mengkaji perihal pengaruh financial distress pada penerimaan opini audit going concern dengan variabel moderasi good corporate governance. Tujuan studi menunjukkan adanya dampak financial distress pada opini audit going concern serta GCG dapat memoderasi relasi financial distress terhadap opini audit going concern. Objek penelitian sektor energi tahun 2014 – 2020 dengan jumlah sampel 273 secara purposive sampling. Metode kuantitatif dengan alat uji analisis menggunakan WarpPLS 7.0. Hasil analisis data yang diperoleh pada penelitian ini, yaitu financial distress berpengaruh negatif pada opini audit going concern serta proporsi dewan komisaris independen dan kepemilikan manajerial tidak mampu memoderasi financial distress pada penerimaan opini audit going concern. Namun, komite audit dan kepemilikan institusional mampu memperlemah hubungan financial distress pada opini audit going concern.